Ex 3 dau coroana!!!!!!!
Anexe:
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
Explicație pas cu pas:
f+g=3x-2+5x+4
f+g= 8x + 2
f-g= 3x-2 -( 5x+4)
f-g= 3x-2 -5x-4
f-g= -2x -6
fg= (3x-2) ori ( 5x+4)
fg= 15x^2 +12x - 10x -8
Fg= 15x^2 + 12x -8
3f= 3 ori (3x-2)
3f= 9x-6
-5g= -5 ori (5x+4)
-5g= -25x-20
f/g= (3x-2) /(5x+4)
g/f= (5x+4) /( 3x-2)
f^2= (3x-2)^2
f^2= 9x^2 - 12x+ 4
g^2=(5x+4)^2
g^2= 25x^2 + 40x+ 16
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă